PENGARUH BERMAIN MUSIK PERKUSI TERHADAP PENINGKATAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DI TK DINIYAH PUTERI PEKANBARU : penelitian skripsi - Mandalika, Bq; Kurnia , Rita; Chairilsyah, Daviq (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fine motor skills in early childhood are abilities related to the coordination of small muscles, especially the hands and fingers, in performing activities such as grasping, folding, cutting, pasting, and other similar tasks. This study was conducted to examine the fine motor skill development of children aged 4–5 years at TK Diniyah Puteri Pekanbaru before and after participating in percussion music activities, as well as to determine the effect of percussion musical instruments on children’s fine motor development. The research applied a quantitative approach using a pre-experimental one group pretest-posttest design. The findings revealed that the use of percussion musical instruments in learning activities had a positive impact on improving children’s fine motor skills, particularly in enhancing hand and finger coordination. In addition, percussion music activities helped children develop concentration, movement accuracy, and coordination between visual responses and hand movements, which are important for writing readiness. Learning activities that combine music and play were also found to create a more engaging and effective learning process for children’s overall development. Therefore, introducing music activities from an early age can support not only fine motor development but also children’s social, cognitive, and musical abilities.